Scheduling Algorithms for 5G Networks and Beyond: Classification and Survey - Mamane, Asmae; Fattah, Mohammed; Ghazi, Mohammed El; Bekkali, Moulhime El; Balboul, Younes; Mazer, Said (IEEE access, 2022)
Over the years, several research groups have been developing effective and efficient scheduling algorithms to enhance the quality of service of mobile communication networks. The arrival of the fifth generation of mobile networks (5G) has demonstrated the importance of advanced scheduling techniques to manage the limited frequency spectrum available while achieving 5G transmission requirements. This issue has been picked up extensively within the research community due to the increasing demand for mobile communications and the desire for a fully connected world. Consequently, the scientific community has developed novel approaches and varied scheduling schemes to meet the needs of various applications and scenario conditions. In this context, this paper presents an overview of the state-of-the-art methods, highlights seminal and innovative research, and investigates the current state of 5G radio resource management. This review of literature compares emerging strategy methods based on their metrics, analyzes their performances, and emphasizes the existing works with a vision for the future of modern 5G and upcoming networks in terms of radio resource allocation to provide a thorough introspection of the literature. Furthermore, gaining a better understanding of the radio resource management state-of-the-art would provide valuable information for future work and might be helpful for new researchers in the field.